2023
DOI: 10.1038/s41598-022-27195-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA extraction methods on CITES-listed timber species and application in species authentication of commercial products using DNA barcoding

Abstract: Quality and quantity of DNA extracted from wood is important for molecular identification of wood species, which can serve for conservation of wood species and law enforcement to combat illegal wood trading. Rosewood (Dalbergia and Pterocarpus) and agarwood (Aquilaria) are the most commonly found hardwood in timber seizure incidents. To monitor international trade of timber and commercial wood products and to protect these endangered wood species from further population decline, in this study, we have compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To accomplish this, it is often necessary to visualize the DNA of interest using techniques such as agarose or polyacrylamide gel electrophoresis 10 , Once the relevant DNA bands have been identi ed, they are directly puri ed from the gel. 11 This extraction is typically performed using commercial kits. However, access to these products is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, it is often necessary to visualize the DNA of interest using techniques such as agarose or polyacrylamide gel electrophoresis 10 , Once the relevant DNA bands have been identi ed, they are directly puri ed from the gel. 11 This extraction is typically performed using commercial kits. However, access to these products is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the chloroplast genome, Internal Transcribed Spacer2 (ITS2) is the non-coding region of the ribosome components in eukaryotes organisms (But et al, 2023). After annotation and contrast of the ITS2 sequences among the seven Leonurus species including the three studied species, we found that the most of nucleotide differences occur after the 57th base from the beginning of the sequence in a total of 221 bases except the species of L. pseudomacranthus showing the signi cant differentia, agreed with the discovery from the group of Dr. Chao and Yang (Yang et al, 2011) (Fig.…”
Section: Comparison Of Its2 Sequences In the Seven Leonurus Speciesmentioning
confidence: 99%
“…Chase et al 2007;Kang et al 2017) DNA extracted from wood of Pterocarpus also shows better ampli cation and high discrimination with ITS2(But et al 2023). In this investigation, a comprehensive analysis was undertaken by comparing the Internal Transcribed Spacer 2 (ITS2) sequences of 30 Andaman padauk accessions with those of 16…”
mentioning
confidence: 99%